2010
DOI: 10.1002/jmri.22396
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose 3D time‐resolved magnetic resonance angiography (MRA) of the supraaortic arteries: Correlation with high spatial resolution 3D contrast‐enhanced MRA

Abstract: Purpose: To evaluate the feasibility of low-dose, 3D timeresolved contrast-enhanced magnetic resonance angiography (TR-CEMRA) in the assessment of the supraaortic vessel, and to compare the results with high-resolution contrast-enhanced MRA (HR-CEMRA). Materials and Methods:This was an Institutional Review Board-approved retrospective study. Forty-five consecutive patients underwent contrast-enhanced 3D TR-CEMRA and 3D HR-CEMRA for evaluation of neurovascular disease at 3.0 T. Gadobutrol was administered at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…[3][4][5][6] Nevertheless, quantitative measurements of blood flow using DSA rarely have been explored. [7][8][9] Recently, Strother et al suggested the color-coded parametric method for illustrating the Tmax of intracranial arteriovenous malformations.…”
mentioning
confidence: 99%
“…[3][4][5][6] Nevertheless, quantitative measurements of blood flow using DSA rarely have been explored. [7][8][9] Recently, Strother et al suggested the color-coded parametric method for illustrating the Tmax of intracranial arteriovenous malformations.…”
mentioning
confidence: 99%
“…Contrarily, time-resolved (TR) techniques (TR-MRA or 4D-MRA), such as TWIST [188], can pick the hemodynamic information by acquiring multiple 3D CE-MRA data sets sequentially but with non-uniform k-space sampling. Indeed, in order to increase the temporal resolution, the central portion of k-space (e.g., 10-20 % that encodes the bulk of the image contrast and should be timed always to occur when the contrast bolus is in the vessels of interest) is acquired more frequently than the peripheral portion.…”
Section: D Tse Sequence (Space)mentioning
confidence: 99%
“…Former studies have established dynamic MRA for assessment of different vascular regions like the peripheral vascular system of the lower extremities, the hands, and supra‐aortic vessels . Therefore, it was of high interest to compare and evaluate dynamic MRA also in diseases of the greater thoracic vessels including acute aortic dissection.…”
Section: Discussionmentioning
confidence: 99%